Politik und Recht erleben, Zukunft mitgestalten - Borck, Paul; Eggers, Frederik; Epperlein, Dinah; Fiesel, Olaf; Fink, Simon; Holst, Eva; Jakob, Lars; Krug, Laura; Leifheit, Svenja; Marquardt, Patrick; Möller, Amelie; Nusser, Julian; et al. (2023)
The transformation towards a carbon-neutral society can only succeed in cooperation with citizens and not against them. This edited volume shows ways to achieve this goal. It presents the results of the interdisciplinary project "Experiencing Politics and Law, Shaping the Future" and the project itself. Citizens were at the centre of the project. Supported by experts in law and political science, they developed ideas on how to improve citizen participation in climate policies. In sum, the contributions form a dialogue between the citizens' perspective, legal and political science analyses and the views of practitioners.